A synopsis of the South American genus Gomphomacromia (Odonata: Gomphomacromiinae) - Von Ellenrieder, Natalia (2005)
Gomphomacromia mexicana is shown to be a junior synonym of G. chilensis based on a comparison of the holotype male with the original description of G. chilensis and specimens identified as that species from Chile. Examination of a large series of specimens from central and southern Chile and Argentina identified both as G. paradoxa and G. etcheverryi shows the proposed diagnostic characters for the two taxa variable, thus G. etcheverryi is considered a junior synonym of G. paradoxa. Illustrated keys, distribution maps and a cladistic analysis for the four known species of the genus are provided.